2016
DOI: 10.3329/jdmc.v24i1.29568
|View full text |Cite
|
Sign up to set email alerts
|

Non Hodgkin’s Lymphoma In Herniated Sigmoid Colon Presenting as Irreducible Left Sided Inguinal Hernia – A Case Report And Review of Literature

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Only one case in the literature is reported as small intestine lymphoma diagnosed as a femoral hernia [ 19 ], and one case is reported of sigmoid colon lymphoma presenting as an irreducible left-sided inguinal hernia [ 4 ]; however, a review of the literature revealed no cases of small intestinal lymphoma presenting as an inguinal hernia (Table 1 ). This is the first reported case to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one case in the literature is reported as small intestine lymphoma diagnosed as a femoral hernia [ 19 ], and one case is reported of sigmoid colon lymphoma presenting as an irreducible left-sided inguinal hernia [ 4 ]; however, a review of the literature revealed no cases of small intestinal lymphoma presenting as an inguinal hernia (Table 1 ). This is the first reported case to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The small bowel [ 2 ] is the second leading site, after the stomach [ 3 ], for primary gastrointestinal non-Hodgkin’s lymphoma (PGI NHL). It commonly causes abdominal pain, changes in bowel habits, weight loss, a palpable abdominal mass and blood in the stool [ 4 ]. The most common histological subtype of PGI NHL is diffuse large B cell lymphoma, for which systemic chemotherapy with rituximab is the most common treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%